O należytym pojmowaniu dziedzictwa narodowego i jego aksjologicznych podstawach - Frankiewicz-Bodynek, Anna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The main purpose of this article is to present the constitutional concept of national cultural heritage in relation to axiological grounds of Polish Constitution such as the principle of human dignity and the principle of common good. First it is necessary to disprove the conclusion of Convention Concerning the Protection of the World Cultural and Natural Heritage that cultural heritage comprise the monuments only. The assumption that intangible cultural heritage fall under the general definition of cultural heritage indicates that cultivation and protection of heritage is the base of the humanity of an individual. Therefore it shall be seen as a implementation of the principle of human dignity. Additionally, it needs to be noted that the principle of common good do not only refer to the state, but also to historical community, culture and traditions. It has been proved that national heritage is one of the common good factors. However the common good shall be perceived as a good of whole community, not as a good of individuals.
Keywords: cultural heritage; national heritage; common good; Intangible heritage; personal dignity; axiology of the constitution